Differentan Wage agricultural Labormanand Women Farm Workers (Qualitative Study of Farm Workers Paddy Field (Oryza sativa L) di Parbul Village Waelata District, Buru Regency) - Siti Fatonah; Junianita. F. Sopamena; Noviar. F. Wenno (Cita konsultindo, 2023)
This study aims to conduct a qualitative study of the factors that cause differences in the wages of male and female agricultural laborers in Parbulu Village, Waelata District, Pick up District. The population in this study were 205 respondents. And the number of samples taken were 31 female farm workers and 30 male farm workers or around 30% of the total population, namely 61 farm workers. Sampling technique based on purpose (Purposive Sampling). The data collected are primary data and secondary data. Data collection methods used are observation methods, interview methods, questionnaire methods, and documentation methods. The type of data used in this research is to use a qualitative approach. And there are several analyzes that are used to analyze qualitative data, namely data reduction, data presentation, drawing conclusions. The results of the data analysis show that the factors that cause differences in the wages of male and female agricultural laborers in the lowland rice commodity are gender, productivity, type of work, time/hours worked. While factors such as age, work experience and the area of ​​land worked do not cause differences in wages.